1995
DOI: 10.1207/s15327752jpa6402_16
|View full text |Cite
|
Sign up to set email alerts
|

Hopkins Symptom Checklist-25, Hmong Version: A Screening Instrument for Psychological Distress

Abstract: The Hopkins Symptom Checklist (HSCL-25; Mattsson, Williams, Rickels, Lipman, & Uhlenhuth, 1969) was translated into the Hmong language and administered to 159 Hmong adults, 73 nonclinical and 86 mental health clients. The instrument demonstrated internal consistency of .97 and had a split-half coefficient of .92 and test-retest reliability of .90. Mental health clients produced scores that were significantly higher than those of nonclinical participants on the Anxiety, Depression, and Total scores. Consistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 4 publications
2
40
0
1
Order By: Relevance
“…The DSHSCL is a 15-item Likert scale that measures symptoms of depression according to the criteria set by the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV). The DSHSCL has been used extensively worldwide in a variety of populations, including refugees (Mollica et al 1987), migrants (McKelvey et al 1993a, b;Mouanoutoua and Brown 1995), and HIVpositive persons in Africa (Kaaya et al 2002), including Southwestern Uganda (Bolton 2001). The DSHSCL has been shown to be valid, reliable, and culturally relevant in these settings (Harvard Program in Refugee Trauma).…”
Section: Methodsmentioning
confidence: 99%
“…The DSHSCL is a 15-item Likert scale that measures symptoms of depression according to the criteria set by the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV). The DSHSCL has been used extensively worldwide in a variety of populations, including refugees (Mollica et al 1987), migrants (McKelvey et al 1993a, b;Mouanoutoua and Brown 1995), and HIVpositive persons in Africa (Kaaya et al 2002), including Southwestern Uganda (Bolton 2001). The DSHSCL has been shown to be valid, reliable, and culturally relevant in these settings (Harvard Program in Refugee Trauma).…”
Section: Methodsmentioning
confidence: 99%
“…The HSCL-10 is a short version of a more comprehensive test . However, the 10-question version performs just as well as the longer versions, and it has been psychometrically established both in population studies and in patient populations (Mouanoutoua & Brown, 1995). In order to impose minimal time and resource demands upon the survey participants, we therefore chose HSCL-10 instead of HSCL-25.…”
Section: Dependent Variablesmentioning
confidence: 99%
“…For instance, when translated into the Mong/Hmong language, the majority of western mental health diagnoses (mental illnesses) simply mean "crazy;" as such, individuals who seek mental health services are stigmatized as incompetent within the Mong/Hmong community (Cerhan, 1990;Mouanoutoua, 2003;Mouanoutoua & Brown, 1995;Nicholson, 1997;Yee, n.d.). Chen, Guarnaccia, and Chung (2003) utilized the Center for Epidemiological Studies Depression Scale (Radloff, 1977) to examine the relationship between acculturation and depression among Chinese and Japanese Americans (n = 102), and found that higher acculturation was associated with greater affective symptoms and fewer somatic symptoms.…”
Section: Depressionmentioning
confidence: 99%
“…Of the current research studies on the Mong/Hmong population, more have focused on the mental health needs of older adults rather than children and young adults (Boehnlein & Kinzie, 1996; R. C. Chung & Lin, 1994;Mouanoutoua & Brown, 1995;Nicholson, 1997;Ying & Akursu, 1997). Furthermore, the availability and development of culturally sensitive and appropriate measurements for the Mong/Hmong population is scarce.…”
Section: Recommendations For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation